Pengaruh Pelatihan Motivasi Berprestasi Terhadap Motivasi Berprestasi Anak Didik Komunitas X - Rio Natannael Wijaya; Mahatma Elok Nuran; Maula Rizka Salsabila; Bernike Hartono; Helen Natalie; Livia Yuliawati; Tifani Meilianawati; Putri Ayu Puspieta; Mopheta Audiola Dorkas (Universitas Ciputra Surabaya, 2022)
This training aimed to determine the effectiveness of achievement motivation training to increase achievement motivation. This research applied a few of McClelland and Alschuler’s Achievement Motivation Training concepts which consists of developing mindset through materials, self-study implemented in study-strategy tests, goal setting, priorities, as well as reflection and self-evaluation, the final results of which will be measured through pretest and post-test. The subjects in this study were 19 students aged 9-14 years who were in elementary and junior high school living in the area of Community X. The sampling technique used was non-probability purposive sampling. This study used Quasi Experiment B, with the research design One Group Pre-test Post-test Design. The measuring instrument used is McClelland's achievement motivation scale which has been adapted into Indonesian. Hypothesis testing was carried out by using parametric statistical tests, namely Paired Sample T-Test to see the effect of training on achievement motivation level. The results of the comparison between pre-test and post-test with paired sample t-test showed p value= 0.46 (p > 0.05). The conclusion is that the hypothesis is rejected, which means that there is no significant effect on the subjects’ achievement motivation before and after the achievement motivation training.